Undaria pinnatifida (Wakame) Intake Ameliorates High-Fat Diet-Induced Glucose Intolerance via Promoting GLUT4 Expression and Membrane Translocation in Muscle - Motoki Imai; Fumitaka Kawakami; Mutsumi Chiba; Makoto Kanzaki; Hiroko Maruyama (Journal of Nutrition and Metabolism)
Type 2 diabetes mellitus (T2DM), a lifestyle-related disease, is developed due to eating habits and decreased physical activity. Diabetes also increases the risk of cancer and major neurodegenerative diseases; controlling the onset of diabetes helps prevent various illnesses. Eating seaweed, such as Undaria pinnatifida (wakame), is a part of the Asian food culture. Therefore, we analyzed the antidiabetic effect of wakame intake using the high-fat diet-induced diabetes mouse model. Furthermore, we analyzed the effect of wakame extract on the cell membrane translocation of glucose transporter-4 (GLUT4) and activation of insulin signal molecules, such as AKT and AMPK, in insulin-sensitive tissues. Differentiated C2C12 cells were incubated with wakame components. The membrane translocation of GLUT4 and phosphorylation of AKT and AMPK were investigated with immunofluorescence staining and Western blotting, respectively. Also, male C57BL/6J mice were fed the normal diet (ND), high-fat diet (HFD), ND with 1% wakame powder (ND + W), or HFD with 1% wakame powder (HFD + W). We evaluated the effect of wakame intake on high-fat diet-induced glucose intolerance using an oral glucose tolerance test. Moreover, we analyzed insulin signaling molecules, such as GLUT4, AKT, and AMPK, in muscle using Western blotting. GLUT4 membrane translocation was promoted by wakame components. Also, GLUT4 levels and AKT and AMPK phosphorylation were significantly elevated by wakame components in C2C12 cells. In addition, the area under the curve (AUC) of the HFD + W group was significantly smaller than that of the HFD group. Furthermore, the level of GLUT4 in the muscle was increased in the wakame intake group. This study revealed that various wakame components exerted antidiabetic effects on the mice on a high-fat diet by promoting glucose uptake in the skeletal muscle, enhancing GLUT4 levels, and activating AKT and AMPK.